Strategi Usaha Mikro dan Kecil Menghadapi Peluang dan Ancaman Pemberlakuan Masyarakat Ekonomi Asean (Studi Kasus Usaha Mikro dan Kecil Kota Depok) - Kautsar, Ikhlash; Suroso, Arief Imam; Hartrisari, Hartrisari (Jurnal Aplikasi Manajemen, 2016)
Indonesia is a country with the largest population in Southeast Asia. This condition causes Indonesia becomes the biggest and the prospective market among other countries. The Enforcement of the ASEAN Economic Community (AEC) in late 2015 caused a major impact on the Indonesian economy, especially among Micro, Small and Medium Enterprises (SMEs). It is causes the reduces of tariff cost of imported product resulting in the increasing number of foreign products into the domestic market. Imported products are known to have quality and better competitiveness than those domestic SMEs such as Malaysia, Singapore, Thailand and Philippine. Therefore, it needs a strategy for the development of SMEs to compete in the era of globalization, particularly the AECÂ